2021
DOI: 10.5435/jaaosglobal-d-21-00091
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Orthopaedic Surgery Residency Application Process During the COVID-19 Pandemic

Abstract: Introduction: The COVID-19 pandemic has led to the cancellation of away rotations and other experiences fundamental to orthopaedic surgery residency application. Limited information is available on the experiences of applicants and program directors (PDs) during the COVID-19 pandemic residency application cycle. This study aimed to evaluate the current perspectives of applicants and PDs regarding the orthopaedic surgery residency application process. Methods: This was a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…Virtual away rotations have rapidly emerged as an innovative response to the cancellation of in-person aways during the pandemic. However, less than half of programs surveyed in this study reported offering a virtual away rotation in 2020, which was similar to the findings of previous studies 11 , 14 . Furthermore, programs ranked in the Doximity top 30 were more likely than lower-ranked programs (OR = 6.75) to offer a virtual away rotation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Virtual away rotations have rapidly emerged as an innovative response to the cancellation of in-person aways during the pandemic. However, less than half of programs surveyed in this study reported offering a virtual away rotation in 2020, which was similar to the findings of previous studies 11 , 14 . Furthermore, programs ranked in the Doximity top 30 were more likely than lower-ranked programs (OR = 6.75) to offer a virtual away rotation.…”
Section: Discussionsupporting
confidence: 90%
“…During the 2020 to 2021 cycle, however, 82% of applicants altered their rank list due to the lack of in-person away rotations 11 . Applicants and program directors also felt that residency program social events during the cycle were not replicated well in the virtual setting 11 . Without adequate opportunities to evaluate each other, unaffiliated programs and applicants may have weighed home program affiliation more heavily when they developed their match rank lists 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without being able to visit the program in-person, the applicant may not have a sense of the program culture, resources available, and whether or not they will enjoy living in the area for a year. 19,20 Similarly, Chandler et al 21 surveyed residents applying to a pediatric surgery fellowship at a single institution and found that only 35% believed that virtual interviews allowed them to decide if the program was the right fit for them. Bamba et al 22 surveyed applicants who interviewed at a plastic surgery residency program and found that those who interviewed in-person felt more acquainted with the program, faculty, and residents more than those who interviewed virtually.…”
Section: Discussionmentioning
confidence: 99%
“…Without being able to visit the program in-person, the applicant may not have a sense of the program culture, resources available, and whether or not they will enjoy living in the area for a year. 19 , 20 Similarly, Chandler et al. 21 surveyed residents applying to a pediatric surgery fellowship at a single institution and found that only 35% believed that virtual interviews allowed them to decide if the program was the right fit for them.…”
Section: Discussionmentioning
confidence: 99%